2021
DOI: 10.1109/access.2021.3093053
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Energy Forecasting Framework Using an Ensemble Deep Learning Approach

Abstract: Industrial and building sectors demand efficient smart energy strategies, techniques of optimization, and efficient management for reducing global energy consumption due to the increasing world population. Nowadays, various artificial intelligence (AI) based methods are utilized to perform optimal energy forecasting, different simulation tools, and engineering methods to predict future demand based on historical data. Nevertheless, nonlinear energy demand modeling is still unfledged for a better solution to ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 60 publications
2
12
0
Order By: Relevance
“…We have found similarities in the results obtained from the other studies we have analysed [44][45][46]. McKinsey's study showed, similar to ours, that teachers save the most time when they use technology to do their pre-class preparations, which are the most time-consuming tasks [35].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We have found similarities in the results obtained from the other studies we have analysed [44][45][46]. McKinsey's study showed, similar to ours, that teachers save the most time when they use technology to do their pre-class preparations, which are the most time-consuming tasks [35].…”
Section: Discussionsupporting
confidence: 86%
“…Many fields, such as forensic science [45], customer service call review and analysis, mental health surveillance, intelligent systems, and educational quality evaluations, pay greater attention to speechbased emotion identification tasks. Deep learning has made it easier to detect emotions in speech, but there are still issues with the study on SER, such as a lack of training data and an insufficient model [46,47]. Speech real-time emotion depends on speakers, cultures, genders, ages, and dialects [48].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the use of deep learning algorithms shows promising in solving recognition or detection challenges such as speech recognition, emotion recognition, face recognition, gesture recognition, and object detection [19]. Nowadays, in addition to the single deep learning model, the hybrid ensemble deep learning model [18,20] is being used in a growing number of research studies. In this regard, the researchers have used several models for emotion recognition, including Convolution Neural network, Deep Belief Network (DBN), Recurrent Neural Networks (RNNs), and Long Short-Term Memory (LSTM) [2,5,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Some of these studies [33] added the impact of COVID-19 on load forecasting using lockdown information as another sequence input. Others [40] use bidirectional LSTM as a learning component. Concerning the previous studies applied to the test data of Kurdistan regional load demand, several studies [46,47] are present.…”
Section: Introductionmentioning
confidence: 99%